Impact of Torrefaction on Fuel Properties of Aspiration Cleaning Residues - Tamelová, Barbora; Malaťák, Jan; Velebil, Jan; Gendek, Arkadiusz; Aniszewska, Monika (Materials (Basel, Switzerland), 2022)
To maximise the use of biomass for energy purposes, there are various options for converting biomass to biofuels through thermochemical conversion processes, one of which is torrefaction. Higher utilisation of waste from the aspiration cleaning of grains, such as wheat or maize, could be one of the means through which the dependence on fossil fuels could be reduced in the spirit of a circular economy. In this study, the effect of torrefaction on fuel properties of agricultural residues was investigated. The tested materials were waste by-products from the aspiration cleaning of maize grains and waste from wheat. The materials were treated by torrefaction under a nitrogen atmosphere (225 °C, 250 °C, and 275 °C), over a residence time of 30 min. During the treatment, weight loss was monitored as a function of time. Proximate and elemental composition, as well as calorific values, were analysed before and after torrefaction. Torrefaction has a positive effect on the properties of the fuels in the samples studied, as shown by the results. The carbon content increased the most between temperatures of 250 °C and 275 °C, i.e., by 11.7% wt. in waste from maize. The oxygen content in the maize waste samples decreased by 38.99% wt. after torrefaction, and in wheat waste, it decreased by 37.20% wt. compared to the original. The net calorific value increased with increasing temperatures of process and reached a value of 23.56 MJ·kg-1 at a peak temperature of 275 °C in by-products from maize. To express the influence of the treatments on combustion behaviour, stoichiometric combustion calculations were performed. Differences of up to 20% in stoichiometric combustion parameters were found between the two types of waste. A similar case was found for fuel consumption, where a difference of 19% was achieved for torrefaction at a temperature of 275 °C, which fundamentally differentiated these fuels.
Keywords: agricultural residues; fuel properties; calorific potential; biochar; torrefaction; stoichiometry